ANALISIS EFEKTIVITAS SIMBG DALAM MENINGKATKAN LAYANAN PERSETUJUAN BANGUNAN GEDUNG DI DPMPTSP KOTA SERANG - Ulfah, Nurul; Bangsawan, Try Adhi; Saepudin, Eli Apud (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
The Serang City Government has implemented a digital-based service system through the Building Management Information System (SIMBG) application, which is one of the updates to public facilities for submitting Building Permits (PBG), particularly for residential functions. This study aims to examine the success of SIMBG implementation in PBG permit services and identify obstacles that affect service quality at the Serang City DPMPTSP. This study uses qualitative research methods. Scientific methods to obtain information were carried out through participatory observation, structured interviews, and documentation studies. The theory used is Sondang P. Siagian’s theory of effectiveness, which has three benchmarks: timeliness, accuracy, and service delivery style. Data analysis was carried out systematically to determine the suitability between the program objectives and implementation in the field. The results of the study show that SIMBG is quite effective in supporting the digitization process of PBG services, but there are still obstacles such as system instability, lack of public understanding, and limitations in internal human resources. Therefore, it is recommended that the government increase socialization, strengthen the technical capacity of officers, and ensure the stability of the SIMBG system for optimal and inclusive public services.